Core Self-Evaluation and Job Satisfaction: Mediating Role of Career Commitment - Sutanti, Meily; Sandroto, Christine Winstinindah (Review of Management and Entrepreneurship, 2021)
This study aims to determine the effect of core self-evaluation on job satisfaction mediated by career commitment in IBM-JTI employees. The sampling technique was convenience sampling, using 86 samples. This research's data analysis method is the mediation test using the Preacher-Hayes The Simple Mediation Model. The results of data processing using SPSS 22 for windows with macros and syntax. This study's results indicate that core self-evaluation and career commitment have a direct effect on job satisfaction. The effect of core self-evaluation on job satisfaction is not mediated by career commitment. Core self-evaluation does not affect career commitment. Keywords: Core Self-Evaluation; Career Commitment; Job Satisfaction